Theoretical principles of market relations in the agricultural sector (Economics and region, 2024)
Agricultural issues have always been and remain the focus of special attention of the world's agricultural scientists and economists. This is not accidental. The development of the agricultural sector has played and continues to play an important role in ensuring the standard of living of the population as a whole. The role and importance of the agricultural sector is great and irreplaceable in ensuring employment of the rural population, solving demographic problems, developing inter-sectorial production and economic relations, ensuring appropriate dynamism in the development of the national economy, and most importantly, food security. According to them, regardless of the economic development model of any state, the development of the agricultural sector is always in the focus of attention of these states, and special attention is paid to the further development of this section. All over the world, agricultural policy is considered a part of economic policy, and in order to implement this policy, appropriate organizational and economic measures are taken at each specific stage of development. In our country, all areas of the economy, including the agrarian sector, have been in a state of economic crisis severeal times at different stages of their development. As the agrarian sector fell into a state of economic crisis, the reasons for its fall into this situation were also investigated by agrarian economist scientists, managers and specialists, appropriate measures were determined and implemented, and the field was brought out of a very difficult and complicated situation. Economically comprehensive development of the country is characterized by a number of indicators, one of wich is the parallel and sustainable development of all regions. The relevance of market relations in the agricultural sector is related to changing demands and development in technology. In modern times, the market relations of the agricultural sector are of great importance. Reasons such as the increase in demand for agricultural products and the expansion of international trade opportunities, innovations in technology, safety of agricultural work, product management, higher expectations of customers about quality, safety and modern standards make market relations in the agricultural sector more relevant and important. The presented article is relevant, it is an issue that is constantly under the attention of the state and society.
Keywords: commodity-money relations; exchange; consumer market; pricing; agriculture; market